The impact of real world information shocks on political attitudes: Evidence from the Panama Papers disclosures - Agnar Freyr Helgason; Vittorio Mérola (Research & Politics, 2022)
The Panama Papers disclosures in April 2016 revealed information about tax avoidance and fraud among political elites and the wealthy on a global scale. But did the disclosures affect relevant political attitudes and behavior, including perceptions of corruption, redistributive preferences, and voting intentions? We leverage nationally representative surveys that were in the field at the time in two heavily impacted countries, France and Spain, and treat the disclosures as a natural experiment, comparing respondents questioned just before and just after the disclosures. Our design highlights the difficulty, at times, of interpreting natural experiments, given the potentially compounded treatments that arise as events unfold over time, and the common inability to properly determine views prior to the treatment. That said, the analysis indicates that the disclosures had limited effects on the domains most likely affected by such a scandal, consistent with them being interpreted based on existing beliefs and identities. Our results thus contradict prior findings which suggest that the Panama Papers had substantial effects on redistributive attitudes, and shed further light on voters’ learning and updating around uncertain, yet emotionally laden, political facts.